Being Good When Not Doing Well: Examining the Effect of the Economic Downturn on Small Manufacturing Firms' Ongoing Sustainability-Oriented Initiatives. (June 2015) - Panwar, Rajat; Nybakk, Erlend; Pinkse, Jonatan; Hansen, Eric
How firms behave under conditions of decline and resource constraints has not been considered in the corporate sustainability literature. This leaves unanswered the question how much we should rely on firms' sustainability-oriented voluntary initiatives at a time when the global economy continues to be weak and firms face persistent threats of decline. In addressing this question, we first argue that the effect of a decline would be different for peripheral and core initiatives. Using data gathered from 478 small firms representing multiple manufacturing sectors in the United States through a survey, we empirically demonstrate that a decline in a firm's financial performance is associated with a higher decline of peripheral initiatives than of core initiatives. We further found that a decline in peripheral initiatives was even greater when a firm operated in a relatively dynamic context. Contextual dynamism, however, did not affect decline in core initiatives.